2016
DOI: 10.1016/j.seizure.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension on admission is associated with a lower risk of early seizures after stroke

Abstract: ES after stroke was equally frequent in patients with ischemic and haemorrhagic stroke. Low/normal blood pressure on admission and younger patient age were risk factors for ES after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…It is well established that hypertension is a major risk factor for ICH; unexpectedly, however, the present study revealed that hypertension was associated with a lower risk of PSE in the multivariable analysis after adjusting for antihypertensive medication use. A prior study by Hundozi et al had similar findings [38]. In their study, patients with hypertension when admitted for stroke had a lower risk of poststroke seizure.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It is well established that hypertension is a major risk factor for ICH; unexpectedly, however, the present study revealed that hypertension was associated with a lower risk of PSE in the multivariable analysis after adjusting for antihypertensive medication use. A prior study by Hundozi et al had similar findings [38]. In their study, patients with hypertension when admitted for stroke had a lower risk of poststroke seizure.…”
Section: Discussionsupporting
confidence: 64%
“…A prior study by Hundozi et al . had similar findings . In their study, patients with hypertension when admitted for stroke had a lower risk of poststroke seizure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic disturbances such as elevated blood glucose or low sodium levels can also precipitate seizures 22 , 30 , 42 , 48 . Low blood pressure and normal lipid levels seem to have protective effect 29 , 44 , 53 . The other risk factors were low ASPECTS score, alcoholism, previous stroke, male gender, and impaired consciousness 28 , 31 , 36 , 45 , 54 (Table 2).…”
Section: Ess After Strokementioning
confidence: 99%
“…[13,15] There are controversial data on the frequency of seizures after CVST; a prevalence of 10% to 50% has been reported. [16] Most of the seizure types are focal seizures. Rarely, lifethreatening generalized tonic clonic-seizures can be seen.…”
Section: Discussionmentioning
confidence: 99%